2018
DOI: 10.12965/jer.1836454.227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise using a mobile device on cardiopulmonary function, metabolic risk factors, and self-efficacy in obese women

Abstract: The purpose of this study was to determine the effects of a 12-week walking exercise using a mobile device on cardiopulmonary function, metabolic risk factors, and self-efficacy in obese middle-aged women. For this study, 14 middle-aged subjects with obesity were included and performed walking exercise of 50%–60% maximum oxygen uptake intensity 3 times a week for 12 weeks. As a result, weight, % body fat, body mass index, and waist circumference significantly reduced. In addition, systolic blood pressure, dias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
1
2
0
3
Order By: Relevance
“…Among health-related physical fitness factors, significant increases were observed in balance and flexibility. Similar findings have demonstrated that walking improved functional physical fitness factors, including flexibility, in middle-aged women (Kim, 2018). The increase in flexibility may be due to the increase range of motion of the hip joints caused by the highly sloped mountain terrain, unlike flat surfaces and thus leading to natural contraction and relaxation of the gastrocnemius muscle and the popliteal muscle above the knee.…”
Section: Discussionsupporting
confidence: 70%
“…Among health-related physical fitness factors, significant increases were observed in balance and flexibility. Similar findings have demonstrated that walking improved functional physical fitness factors, including flexibility, in middle-aged women (Kim, 2018). The increase in flexibility may be due to the increase range of motion of the hip joints caused by the highly sloped mountain terrain, unlike flat surfaces and thus leading to natural contraction and relaxation of the gastrocnemius muscle and the popliteal muscle above the knee.…”
Section: Discussionsupporting
confidence: 70%
“…Walking reduced possibility of cardiovascular diseases, moreover, it helps to prevent obesity (Campaña and Costa, 2017; Kim, 2018; Ryew and Hyun, 2016). But when gait continued for long time, it may not be maintained a normal gait mechanism and controllability under condition of external force (collision), foot obstacle, sloping load and slipping etc.…”
Section: Discussionmentioning
confidence: 99%
“…Recently exercise participants preferring physical activities like long-time trekking, climbing, and walking for purpose of weight reduction, exercise rehabilitation, health and wellbeing etc. had been increased (Campaña and Costa, 2017; Kim, 2018; Ryew and Hyun, 2016). Like these, it is necessary to induce fatigue through long-time walking, but relation of these variables related with power is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Terjadi penurunan berat badan secara signifikan (-5,9 kg; p <0,001) setelah melakukan latihan ketahanan, 9 (-5,6 kg; p <0,001) setelah melakukan exercise, 10 (-1,46 kg; p= 0,005) setelah melakukan aerobik dan latihan jalan, 12 (−2,6 kg; p <0,001) setelah melakukan latihan intensitas tinggi, 14 dan adanya perubahan penurunan berat badan sebesar (−10,5 kg; p <0,001) dengan melakukan latihan aerobik berupa kombinasi lompatan. 15 Namun, satu artikel dari Gondim 11 menemukan bahwa latihan fisik tidak berpengaruh secara signifikan terhadap penurunan berat badan pada orang dengan obesitas.…”
Section: Metode Penelitianunclassified
“…Dari ketujuh artikel tersebut diperoleh hasil bahwa latihan fisik memengaruhi penurunan kolesterol. Terjadi penurunan kolesterol secara signifikan (-23 mg/dl; p <0,01) setelah melakukan latihan ketahanan, 9 (-22 mg/dl ; p <0,0001) setelah melakukan exercise, 10 (-6; p <0,01) setelah melakukan latihan fisik, 11 (-6,86 mg/dl; p=0,618) setelah melakukan aerobik dan latihan jalan, 12 (-9 mg/dl; p=0,001) setelah latihan fisik dan menjaga diet, 13 (-5,1 mg/dl; p= 0,001) setelah melakukan latihan intensitas tinggi, (-7,94%; p=0,001) setelah melakukan latihan aerobik berupa kombinasi lompatan. 15 Aktivitas fisik yang dapat menurunkan berat badan dan kolesterol dapat berupa latihan ketahanan seperti treadmill, sepeda statis, dan rowing technic yang diberikan selama 3 kali per minggu selama 12 minggu; 9 latihan fisik 3-6 kali per minggu dengan intensitas sedang atau tinggi yang dipandu oleh instruktur; 10 latihan aerobik yang dilakukan dengan latihan jalan kaki berdurasi selama 60-80 menit; 12 latihan intensitas tinggi; 14 serta latihan fisik yang dilakukan melalui tahapan 5-10 menit pemanasan, diikuti dengan latihan rutin aerobik berupa kombinasi lompatan, dan 5-10 menit pendinginan.…”
Section: Metode Penelitianunclassified